Modeling the Formation of Professional Competence of Future Programmers Through the Development of Fundamental Knowledge and Skills - Khayitov Bakhodir Yusufovich (Genius Journals, 2022)
This article presents recommendations on the development of a model for the formation of professional competence of students in the "Computer Engineering" specialty by developing fundamental knowledge
Keywords: Modeling, graphic, heuristic, model, competent, Technological component, programming